"There Are Four Greats in the Realm": Looking at the Evolution of the Laozi Text with Respect to Different Orderings of the "Four Greats". Issue 3 (3rd July 2017) - Jing, Chen
EDITOR'S ABSTRACT: This paper discusses the two different versions of section 25 of the received Laozi concerning the "four greats in the realm, " one beginning with "the Way is great" and the other with "heaven is great." While both can be textually supported, this paper argues that the latter is not an error, but rather belongs to an early version of the Laozi . The transmitted edition, however, begins with "the Way is great, " which shows that this version ultimately won out over the former. This paper examines the Han dynasty Laozi commentaries showing the influence of Han dynasty cosmogonies on the ultimate success of the order prioritizing the Way in the transmitted edition.